SARS-CoV-2 reinfection with a virus harboring mutation in the Spike and the Nucleocapsid proteins in Panama. (July 2021) - Díaz, Yamilka; Ortiz, Anyuri; Weeden, Adriana; Castillo, Daniel; González, Claudia; Moreno, Brechla; Martínez-Montero, Mabel; Castillo, Marlene; Vasquez, Grettel; Sáenz, Lisseth; Franco, Danilo; Pitti, Yaneth; et al.
Graphical abstract: Highlights: SARS-CoV-2 reinfection by viruses from 2 different endemic lineages from Panama. Both infections caused mild symptoms in immunocompetent patient with no comorbidities. Reinfection has 21 nucleotide substitutions, 1 deletion, 1 insertion compared to 1st. Amino acid changes in the Spike, orf1a, helicase, orf3a, N proteins. Spike mutations D614G, L452R in 2nd virus: better transmission and immune escape. Abstract: We report a case of reinfection by SARS-CoV-2 with the second virus harboring amino acid changes in the Spike protein (141-143del, D215A, ins215AGY, L452R, D614G), orf1a, helicase, orf3a, and Nucleocapside. The virus associated with the reinfection, from an endemic lineage containing the S:L452R immune escape mutation, was circulating in Panama at the time.